Preparation and characterization of grease formulated from waste transformer oil - Siti Nur Atiqah, Mohd Sofi; Mohd Aizudin, Abd Aziz; Nur Suhaila, Anang Japar; Nurul Waheeda, Abdu Rahman; Mohd Yusri, Mohd Yunus (IOP Publishing, 2019)
Grease is known as a lubricating material in a form of solid to semisolid mixture which is produced with the combination of base oil (80% - 95%), thickener (2% - 15%) and additive (0% - 10%). The limitation of soap grease performances as well as the volatile oil prices worldwide has led the interest in seeking alternative grease formulation. This research is focusing on the formulation of non-soap based grease from waste transformer oil (WTO) by two types of non-soap based thickeners, i.e. fumed silica and bentonite. The grease is prepared using different ratios of WTO and non-soap thickener ranging from 90:10 to 65:35. The physical and chemical properties of the formulated grease were evaluated using the ASTM International grease testing standard – for consistency and oil separation, and using the thermalgravimetric analyzer (TGA) and Fourier Transform Infrared Spectroscopy (FTIR) – for thermal stability and composition identification. It was found that the grease consistencies were directly proportional to the amount of thickener and the oil separated from the grease will affect the grease stability. Greases were found thermally stable at temperature as high as 150 °C. From the overall test, the best formulation was the grease formulated using bentonite with the ratio of 80:20 with NLGI grade 2 consistency.